2022
DOI: 10.1186/s12890-022-02044-5
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of non-invasive ventilation and long-term oxygen treatment in Helsinki University Hospital area, Finland

Abstract: Background Chronic respiratory failure (CRF) can be treated at home with non-invasive ventilation (NIV) and/or long-term oxygen (LTOT). The prevalence of these treatments is largely unknown. We aimed to clarify the prevalence and indications of the treatments, and the three-year mortality of the treated patients in the Helsinki University Hospital (HUH) area in Finland. Methods In this retrospective study we analyzed the prevalence of adult CRF pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous data have shown that home invasive mechanical ventilation is uncommon in Finland and becoming even more so [34]. In contrast, NIV and/or long-term oxygen are common treatments for chronic respiratory failure in Finland [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have shown that home invasive mechanical ventilation is uncommon in Finland and becoming even more so [34]. In contrast, NIV and/or long-term oxygen are common treatments for chronic respiratory failure in Finland [35].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent hypercapnic failure is defined as a partial pressure of carbon dioxide (PaCO 2 ) > 6 kPa, combined with elevated levels of standard bicarbonate (HCO 3 ) > 26.9 mmol/L (males)/26.2 mmol/L (females), and base excess (BE) > 3 mmol/L in an arterial blood gas analysis, carried out whilst the patient is in a stable phase [ 5 ]. As with persistent hypoxic failure, the literature is sparse on the prevalence of persistent hypercapnic failure, but in European cohorts of patients with very severe COPD, a prevalence of 22–25% is seen [ 6 , 7 ]. The prevalence of combined persistent hypoxic and hypercapnic respiratory failure is not described in the literature.…”
Section: Introductionmentioning
confidence: 99%